(untitled) (Global Journal of Human-Social Science, 2024)
The excessive use of both licit and illicit drugs has shown a great growth during the last years, the use of licit drugs is a complex issue, as it involves several subsystems of individual and social life. Studies in this area help in understanding the different socio-cultural aspects. This study aims to characterize the profile of alcohol and cigarette users seen at the Jardim Monte Verde-PE family health unit. In order to characterize the profile of the participants, a descriptive quantitative approach study was carried out at the USF Jardim Monte Verde. The sample consisted of 50 subjects (25 cigarette users and 25 alcohol users), aged between 18 and 60 years of both genders. Data collection was performed through semi-structured interviews and analysis of medical records. The results obtained by the scale with some variables related to smoking and alcohol consumption and the self-assessment of self detected the main psychosocial aspects related to cigarette and alcohol consumption. The production of knowledge regarding the profile of alcohol and cigarette users is considered, reflecting on actions and the work process that involves the theme of their use in primary care.